Earliest documented report of Scleroderris canker in North America: damage believed until now to be caused by summer frost - Laflamme, Gaston (Phytoprotection, 2009)
In 1934, over 200,000 red pine (Pinus resinosa) seedlings were planted at Valcartier, near Quebec City. By 1939, more than 28% of these pines were dead. Fifteen years after plantation, red pine mortality reached 93% and the plantation was considered a total loss. Summer frost was thought to be the cause of red pine mortality, while white pine (Pinus strobus) trees planted at the same time were killed by white pine blister rust (Cronartium ribicola), without any trace of frost damage. However, while summer frost was not listed in insect and disease survey reports published from 1953 to 1993, it was reported in the Valcartier area. Analysis of archival documents and publications shows that Scleroderris canker caused by Gremmeniella abietina was responsible for this mortality. This disease was not known in Canada before 1960. Our diagnosis is based on the description of signs and symptoms, on photographs of damage and on samples collected on site. Gremmeniella abietina, North American race, was isolated and identified. The age of the trees confirms the identity of the plantation; the age of the cankers on residual pines shows that the disease reached the trunks around 1945. High snow depth - not frost - in topographic depressions created conditions conducive to the development of the disease at the epidemic level. This is the earliest documented report of Scleroderris canker in North America.